Determination of the stability boundaries for the hamiltonian systems with periodic coefficients - Prokopenya, A. N. (Mathematical Modelling and Analysis, 2005)
We consider the hamiltonian system of linear differential equations with periodic coefficients. Using the infinite determinant method based on the existence of periodic solutions on the boundaries between the domains of stability and instability in the parameter space we have developed the algorithm for analytical computation of the stability boundaries. The algorithm has been realized for the second and the fourth order hamiltonian systems arising in the restricted many‐body problems. The stability boundaries have been found in the form of powers series, accurate to the sixth order in a small parameter. All the computations are done with the computer algebra system Mathematica. Hamiltono sistemų su periodiniais koeficientais stabilumo tyrimas begalinių determinantų metodu Nagrinėjama Hamiltono tiesinių diferencialinių lygčių su periodiniais koeficientais sistema. Remiantis tuo, kad parametrų erdvėje stabilumo ir nestabilumo sritis skiriančioje sienoje egzistuoja periodinis sprendinys, sukurtas analitinis minėtos sienos apskaičiavimo algoritmas. Algoritmas realizuotas antros ir ketvirtos eiles Hamiltono sistemoms, kylančioms nagrinėjant apribotų keleto kūnu uždavinius. Stabilumo srities siena randama laipsninės eilutės pavidalu mažojo parametro šešto laipsnio tikslumu. Skaičiavimai atlikti skaičiavimo algebros paketo Mathematica pagalba. First Published Online: 14 Oct 2010